STRATEGI PEMASARAN AQIQAH MANDIRI DAN CATERING DALAM MENINGKATKAN OMSET PENJUALAN - Fitriyani Nur Sa’adah; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
The more advanced the times and changes in human life patterns cause human needs to also change, one of which is primary needs, especially in terms of food and drink. The increasing need for food, of course, will bring business opportunities, one of which is the aqiqah & catering business. One of these businesses in Surabaya is Aqiqah Mandiri & Catering. Aqiqah Mandiri & Catering is a business engaged in services and catering which is one of the shelters of Yatim Mandiri. The Aqiqah Mandiri & Catering business is classified as superior and has a good enough potential to develop. Competition in the business world is getting wider, causing companies to have a good marketing strategy to increase sales turnover. With regard to the business strategy carried out by Aqiqah Mandiri & Catering, researchers are interested in studying the marketing strategy implemented by Aqiqah Mandiri & Catering to increase sales turnover. This research is a qualitative descriptive research. The data sources obtained are primary and secondary data. Data collection techniques were carried out by observation, interviews and documentation. Data analysis techniques used data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that Aqiqah Mandiri & Catering in marketing implements the 7P strategy which includes product, price, place, promotion, process, people and physical. Of the seven strategies, the most dominant in increasing sales turnover is the product, price and promotion strategy. The marketing strategy applied also does not deviate from Islamic economic principles. Keywords: Marketing strategy, sales turnover, Marketing mix